On the fast economic growth of small countries specialised in tourism - Alessandro Lanza; Francesco Pigliaru (Fondazione Eni Enrico Mattei (FEEM), 1998)
Having grown faster than world GDP since the 1950s, international tourism is today one of the most important tradable sectors, with expenditure on tourist goods and services representing some 8% of total world export receipts and 5% of world GDP. Starting from a broad perspective, two main facts could be pointed out: a) countries specialised in the tourism sector have experienced in the recent past a good economic performance and b) they have a (relatively) small dimension. This paper examines these facts considering with particular attention the dimension point of view. We use a two-sector endogenous growth model to define the conditions required for small countries with a relative large endowment of natural resource to specialise in tourism and to enter the faster growth path. A model based on the size of the natural resource suitable for tourism development is presented and discussed.
Keywords: 330; Neue Wachstumstheorie; Internationale Arbeitsteilung; Tourismus; Kleines-Land-Modell; Theorie